Pemetaan Lokasi Evakuasi Bencana Alam Tsunami dengan Virtual Reality 360 Derajat - Susanto, Agus; Purwaningrum, Santi; Setiawan Prabowo, Annas (P3M Politeknik Negeri Cilacap, 2024)
The rapid development of information technology is encouraging innovation in various fields, including in the field of geographic disaster information services. The tsunami natural disaster is a serious threat to Cilacap district which has a fairly long coastline. When a natural disaster occurs, the first thing that victims of a natural disaster must do is take cover and look for the location that is considered the safest to save themselves. To increase community preparedness for potential tsunami risks, this research aims to develop evacuation location mapping using virtual reality technology in a 360 degree format specifically in Cilacap district. This research method has 2 stages, namely the literature study stage and the system development stage. The literature study stage begins with conducting direct observations and interviews with the Cilacap Regency BPBD. Meanwhile, the second stage is the system development stage which will be carried out using the extreme programming method which includes planning, designing, coding and system testing activities by implementing the System Usability Scale (SUS) method. The result of this research is an application for mapping natural disaster evacuation locations with the test results using the SUS method getting a score of 81. The practical implication of this research is that it can be a basis for related parties to design and implement more effective disaster mitigation strategies in Cilacap district.